Impact of Arctic shelf summer stratification on Holocene climate variability. (1st July 2018) - Thibodeau, Benoit; Bauch, Henning A.; Knies, Jochen
Abstract: Understanding the dynamic of freshwater and sea-ice export from the Arctic is crucial to better comprehend the potential near-future climate change consequences. Here, we report nitrogen isotope data of a core from the Laptev Sea to shed light on the impact of the Holocene Siberian transgression on the summer stratification of the Laptev Sea. Our data suggest that the oceanographic setting was less favourable to sea-ice formation in the Laptev Sea during the early to mid-Holocene. It is only after the sea level reached a standstill at around 4 ka that the water column structure in the Laptev Sea became more stable. Modern-day conditions, often described as "sea-ice factory", were reached about 2 ka ago, after the development of a strong summer stratification. These results are consistent with sea-ice reconstruction along the Transpolar Drift, highlighting the potential contribution of the Laptev Sea to the export of freshwater from the Arctic Ocean. Highlights: We reconstructed variation in nutrient utilization over the Laptev Sea throughout the Holocene. The Holocene Siberian transgression modulated the water column structure and created unstable conditions until 4 ka. Oceanographic conditions favourable to the onset of the Laptev Sea 'sea-ice factory' were reached around 2 ka.